(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article is devoted to a comprehensive analysis of the effectiveness of the taxation system for participants in free economic zones in the Republic of Uzbekistan in stimulating the export potential. The study provides an in-depth study of macroeconomic indicators, investment flows and the dynamics of foreign trade turnover for 2023–2025. The compliance of the established profit tax, property and land tax preferences for free economic zones with international tax coordination, in particular, BEPS (Base Erosion and Profit Shifting) Action 5 and the requirements of the World Trade Organization is scientifically assessed. The report analyzes the structural problems in Uzbekistan ’s export structure, including the concentration of raw materials and the low technological complexity of products, and indicates ways to improve tax mechanisms to eliminate them. A comparative analysis is conducted with successful models of countries such as Turkey and China, and practical proposals are developed to increase the competitiveness of the national economy.